Les langues gbè dans les premiers écrits européens - ADJERAN, Moufoutaou et al. (My University, 2023)
This article looks at the early contacts between Portuguese and Spanish on the one hand, and the populations of the West African coastal area between eastern Ghana and western Nigeria on the other, and more specifically at the first two descriptions, in European languages, of the Gbe languages. The former date back to 1658; it bears no author’s name and is entitled: Doctrina christiana; y explicacion de sus Misterios, en nuestro idioma español, y en lengua Arda. Our source is its reproduction in Labouret and Rivet (1929). The latter, by Antonio da Costa Peixoto, dates back to 1741 and is entitled Obra nova de Lingoa Geral de mina traduzida, ao nosso Igdioma. Our source is its reproduction by Silveira (1944). The article deals with the difficulties inherent in these writings, aside the historical interest they represent. The first text, which announces the language of Arda, confuses the glossonym with the name of the Kingdom of Allada, whereas the second text clearly identifies the glossonym. Furthermore, the transcription (segmental and suprasegmental) of the texts in the two documents studied is a source of semantic and syntactic disturbances. The lack of explicit transcription rules adds to the impossibility of highlighting them due to the irregularity of the transcriptions. The methods used are based on the search for semantic equivalents in several current Gbè languages.
Keywords: Gbè languages; European descriptions of Africa; spelling of African languages; interpretation of African languages